2004
DOI: 10.1186/1471-244x-4-34
|View full text |Cite
|
Sign up to set email alerts
|

Psychological trauma and evidence for enhanced vulnerability for posttraumatic stress disorder through previous trauma among West Nile refugees

Abstract: Background: Political instability and the civil war in Southern Sudan have resulted in numerous atrocities, mass violence, and forced migration for vast parts of the civilian population in the West Nile region. High exposure to traumatic experiences has been particularly prominent in the Ugandan and Sudanese of the West Nile Region, representing an indication of the psychological strain posed by years of armed conflict.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
316
2
15

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 383 publications
(373 citation statements)
references
References 17 publications
36
316
2
15
Order By: Relevance
“…At the same time, the previously experienced traumatic events have probably increased the vulnerability for posttraumatic symptoms related to the tsunami. The finding that previous traumatic exposure is a significant predictor for the development of disaster-related PTSD supports a general dose-effect model of PTSD (Neuner et al, 2004) and might help to explain why PTSD rates after disaster are higher in developing countries, which are often characterized by high levels of violence.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…At the same time, the previously experienced traumatic events have probably increased the vulnerability for posttraumatic symptoms related to the tsunami. The finding that previous traumatic exposure is a significant predictor for the development of disaster-related PTSD supports a general dose-effect model of PTSD (Neuner et al, 2004) and might help to explain why PTSD rates after disaster are higher in developing countries, which are often characterized by high levels of violence.…”
Section: Discussionsupporting
confidence: 58%
“…For example, Bremner, Southwick, Johnson, Yehuda, and Charney (1993) showed that Vietnam veterans who had a previous history of childhood abuse were at higher risk for PTSD. In a study of civil war adult victims in Africa, a clear linear relationship between the number of traumatic event types and posttraumatic stress could be confirmed (Neuner et al, 2004).…”
mentioning
confidence: 91%
“…However, the PTSD rate of 13% found in the semi-structured clinical interviews is comparatively low (Alpak et al, 2015; Führer et al, 2016), with a high number of participants showing a sub-syndromal PTSD (22%). Since PTSD depends on the cumulative exposure to traumatic stressors (Kolassa et al, 2010; Neuner et al, 2004), the PTSD rate will vary with the severity and frequency of life-threatening experiences. Further, manifest PTSD symptoms in refugees often appear after some time, when the so-called ‘honeymoon phase’ of euphoria and relief has passed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Psychometric questionnaires included the trait measure of the State-Trait Anxiety Inventory (STAI) (Laux et al, 1981), Beck Depression Inventory (BDI) (Hautzinger et al, 1994), and Dissociation Experience Scale (DES) (Spitzer et al, 1998). Traumatic load was estimated by assessing the number of different traumatic event types experienced or witnessed (Neuner et al, 2004) as reported in the Posttraumatic Stress Diagnostic Scale (PDS) (Ehlers et al, 1996). The study protocol was approved by the local ethics committee.…”
Section: Participantsmentioning
confidence: 99%